The Role of Municipal Administration in Adjusting the System of Trade and Service - Vengrauskas, Vytautas; Bagdonienė, Liudmila; Žitkienė, Rima (Ekonomika, 1999)
The goal is to show the role of municipal administration when solving such sore social problems as pupils and students’ catering, network of trade and service enterprises, and its dislocation in the country. According to the research made the present situation and possible ways of their solution are analyzed. The investigation data show some improvement in the dislocation of trade, catering, and household service enterprises. The current law of municipal administration does not solve the problem of adjusting the system of trade and service. The government, municipal administrations have to create similar conditions to all inhabitants to purchase goods, to get the service they wish. It means these and some other state institutions have to coordinate the creation of the systems of trade service and service rendering. The experience of European countries shows that the improvement of the above mentioned systems is not left to itself, i. e. to market self-regulation. It is suggested to prepare the conception of trade and service system that would be more detailed in separate programs. The authors agree with F. Tannery that the sphere of service having been highly increased it is necessary to have its development strategy the three dimensions of which - territory expansion, coordination of service activity, and substantiation of service development - are to be taken into account when creating it. The strategies of service development should be of state and local levels as well. Planning of the development of state territory creates the conditions to have equal conditions of living all round the country, to form the policy of the development of residential areas and infrastructure systems, etc. The state leads the coordination strategy determining the priorities of economic activity and making the certain preconditions to carry out such the activity. Town authorities (municipal administration and council) affirm and accomplish the general plan of territory development in which the development of industrial activity, residential areas, recreation zones, etc. are considered. The municipal administration ought to consider the necessity of the development of service infrastructure. To fulfill this one has to use economical and financial possibilities of the market economics.